Pyrometallurgical treatment of jarosite residue with a mixture of CaO, SiO2, and CaSi - Jiménez-Lugos C.; Flores-Favela M.; Romero-Serrano A.; Hernández-Ramírez A.; López-Rodríguez J.; Cruz-Ramírez A.; Colin-García E. (Journal of Mining and Metallurgy. Section B: Metallurgy)
During the electrolytic production of zinc, the iron in solutions is mainly controlled by the precipitation of jarosite. This precipitate also contains valuable metals (Zn, Pb, Cu, Ag) and toxic elements (Hg, Cd, As). This study deals with the pyrometallurgical treatment of jarosite waste in order to recover the metal values and convert the waste into environmentally acceptable slag. Initially, the sample was heated to 100°C to remove moisture, and then roasted at 700°C to release some OH‒ and sulfate groups by thermal decomposition. The analysis of the SiO2-CaO-Fe2O3 ternary phase diagram showed that a flux containing 48% CaO and 52% SiO2 can be used to melt the roasted jarosite at 1400°C. Subsequently, tests were carried out with the reducing agent (CaSi), resulting in a mixture of slag and two metallic phases, one of which is an Fe-Si alloy and the other a Pb-rich phase containing the valuable metal Ag. Both the metallic and slag phases were characterised by chemical analysis, SEM-EDS and XRD. Additionally, the raw jarosite residue and the final slag were leached with an aqueous acetic acid solution to estimate their chemical stability. The obtained results show that the slag produced after the reduction of jarosite residue meets the environmental specifications and could be used as raw material in other industries.